창업가의 개인적 특성과 창업역량 간의 관계에서사회적 네트워크의 매개효과 - 신은영; 이주연 (시스템엔지니어링학술지, 2024)
The purpose of this study is to provide basic data to help start-up performance by cultivating entrepreneurial capacity by identifying the effect of individual characteristics of entrepreneurs on entrepreneurial capacity through social network. In order to achieve the purpose of the study, an online survey was conducted in the metropolitan area, and the results were presented using the SPSS 27 statistical program. First, as a result of examining the correlation between personal characteristics, social networks, and entrepreneurial capabilities, there was a positive correlation between social networks and personal characteristics, a positive correlation between social networks and entrepreneurial capabilities, and a positive correlation between personal characteristics and entrepreneurial capabilities. Second, the mediating effect of social networks was partially mediated in the relationship between personal characteristics and entrepreneurial capabilities of entrepreneurs. Therefore, in order to foster entrepreneurial capabilities of entrepreneurs, it is necessary to understand the tendencies of entrepreneurs and increase sustainable competitiveness and success rates in market competition. In addition, in order to predict follow-up results and derive effective strategies for policy support, it will be important to utilize personal characteristics and social networks together to develop policies and support programs.
Keywords: Creator; Personal Characteristics; Creativity; Social Networking; Mediating Effect